Pengajaran Kritik Seni Kontemporer melalui Pendekatan Semiotika - Sumarwahyudi Sumarwahyudi (Mahesa Research Center, 2021)
This article is about teaching art criticism in college. Nowadays, the use of approaches that are not conventional, or only using a formalistic approach, is starting to bloom. This is because to discuss contemporary artworks that discourse increasingly diverse contemporary ideas, it is even more difficult to interpret them as an alternative to using a semiotic approach. One of them refers to the thought of Umberto Eco. One theory that can be used is called the